2013
DOI: 10.1186/1475-2891-12-87
|View full text |Cite
|
Sign up to set email alerts
|

Daily consumption of a synbiotic yogurt decreases energy intake but does not improve gastrointestinal transit time: a double-blind, randomized, crossover study in healthy adults

Abstract: ObjectiveProbiotic and synbiotic products are widely marketed to healthy individuals, although potential benefits for these individuals are rarely studied. This study investigated the effect of daily consumption of a synbiotic yogurt on gastrointestinal (GI) function in a sample of healthy adults.Subjects/MethodsIn a randomized crossover double-blind study, 65 healthy adults consumed 200 g/day of yogurt with (synbiotic) or without (control) added probiotics (Bifidobacterium lactis Bb12, Lactobacillus acidophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 47 publications
0
7
2
1
Order By: Relevance
“…Similarly, previous studies showed no differences in the hunger ratings of healthy young adults between yogurts with or without 6 g of inulin in a one-time consumption basis [26]. Other studies in which inulin intake showed an effect on appetite control include two-weeks of repeated consumption of symbiotic yogurts containing 4 g of inulin, which reduced the reported energy intakes [27]; and, eight-day consumption of yogurts containing 6 g of inulin, which significantly lowered the "desire to eat" and "prospective food consumption" ratings [28]. There is no previous research on the effect of coffee-cascara on appetite modulation.…”
Section: Discussionmentioning
confidence: 51%
“…Similarly, previous studies showed no differences in the hunger ratings of healthy young adults between yogurts with or without 6 g of inulin in a one-time consumption basis [26]. Other studies in which inulin intake showed an effect on appetite control include two-weeks of repeated consumption of symbiotic yogurts containing 4 g of inulin, which reduced the reported energy intakes [27]; and, eight-day consumption of yogurts containing 6 g of inulin, which significantly lowered the "desire to eat" and "prospective food consumption" ratings [28]. There is no previous research on the effect of coffee-cascara on appetite modulation.…”
Section: Discussionmentioning
confidence: 51%
“…The mean transit time of the colon was estimated at approximately 30 hours [12, 13]. Therefore, subjects had to ingest the activated core temperature pill twenty-four hours prior to the visits to assure that the pill was located in the colon at the time the measurements took place.…”
Section: Methodsmentioning
confidence: 99%
“…Core body temperature was measured using a VitalSense® Core temperature capsule, and data were analysed using Equivital TM Manager (Hidalgo Limited, Cambridge, United Kingdom) core temperature pill. The mean transit time of the colon was estimated at approximately 30 hours [ 12 , 13 ]. Therefore, subjects had to ingest the activated core temperature pill twenty-four hours prior to the visits to assure that the pill was located in the colon at the time the measurements took place.…”
Section: Methodsmentioning
confidence: 99%
“…Os lactobacilos são reconhecidos por sua atuação na promoção de saúde e manutenção equilibrada da microbiota intestinal na qual, pode diminuir os procesos putrefativos por reduzir o acúmulo de substâncias nocivas no trato gastrointestinal. A presença de níveis elevados de bacterias bífidas está relacionado com uma microbiota intestinal saudável em todas as fases de vida da espécie humana [27,28].…”
Section: Formulaçõesunclassified